Micronutrient availability in soils of Northwest Bosnia and Herzegovina in relation to silage maize production - Djordje Grujcic; Milanka Drinic; Iva Zivanovic; Ismail Cakmak; Bal Ram Singh (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2018)
Maize (Zea mays L.) is the most widely grown crop in Bosnia and Herzegovina especially in Northwest part of the country. Considering that, the maize is extremely sensitive to micronutrient deficiency the main aim of this study was to asses: (1) micronutrient availability in soil, (2) micronutrient status in silage maize; and (3) the relationship between micronutrient soil availability and maize plant concentration. Soil samples for micronutrient availability (n = 112) were collected from 28 farms in 7 municipalities. Plant available micro- and macro- nutrients in soil were extracted using Mehlich-3, except plant available Se was extracted using 0.1M KH2PO4. Result showed that on average there was no significant difference between different soil types regarding their potential in plant available nutrients. P deficiency was present both, in soil and plants in whole region. Soil extractable P was ranging from 0.003–0.13 g kg−1 and total plant P was ranging from 0.79–4.95 g kg−1. Zinc deficiency was observed in two locations both in soil (0.71 mg kg−1; 0.79 mg kg−1) and plant (11.5 mg kg−1; 15.8 mg kg−1). Potential Se soil deficiency was observed on some locations, while Se plant status is not high enough to meet daily requirements of farm animals. Extractable soil nutrients could be used as relatively good predictor of potential soil and plant deficiencies, but soil nutrient interactions and climate conditions are highly effecting the plant uptake potential.